A Tale from the Care Bares: The Witch Down the Street - Morgan, Stephanie; Cooke, Tom. ([Beverly, Mass.] : Parker Brothers, 1983)
Three Care Bears from the land of Care-a-lot help Melissa see that the woman she thought was a witch is just a lonely old lady.
Ill. on lining papers.
"Ages 4 to 8"--Cover.
Keywords: Care Bears